2003
DOI: 10.1002/mds.10313
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of individual finger movements in Parkinson's disease

Abstract: By analyzing the kinematics of repetitive, constant-amplitude, finger oppositions, we compared the impairment of individual and nonindividual finger movements in patients with Parkinson's disease. In one task, subjects tapped only the index finger against the thumb (individual oppositions); in the other task, they tapped all four fingers together against the thumb pad (nonindividual oppositions). We used an optoelectronic motion analysis system to record movements in three-dimensional space and recorded three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 22 publications
4
66
0
Order By: Relevance
“…Results demonstrated that in the more advanced stages of PD, neurotransmitters in a particular module may be depleted to such an extent that further movement by that module is completely prevented until the neurotransmitters have been allowed to re-accumulate to a certain level. This may explain the increased inter-segment delay observed in PD patients between movement segments of a sequential movement (Berardelli et al 2001;Agostino et al 2003;Kelly and Bastian 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results demonstrated that in the more advanced stages of PD, neurotransmitters in a particular module may be depleted to such an extent that further movement by that module is completely prevented until the neurotransmitters have been allowed to re-accumulate to a certain level. This may explain the increased inter-segment delay observed in PD patients between movement segments of a sequential movement (Berardelli et al 2001;Agostino et al 2003;Kelly and Bastian 2005).…”
Section: Discussionmentioning
confidence: 99%
“…PD patients exhibit abnormal pauses between movement segments and a more pronounced movement time when a task is performed within a sequence of moves (Suri et al 1998;Berardelli et al 2001). Several mechanisms have been proposed to explain the extra deficits observed in complex movements, such as insufficient dopamine resources for multiple simultaneous movements, difficulty in switching between movement segments due to impaired force control, interference from competing motor programs, and impaired preparation of movement sequences (Agostino et al 2003;Levy et al 2002). Cutsuridis and Perantonis (2006) have developed a basal ganglia-corticospinal network model for control of voluntary arm movements by incorporating dopaminergic innervation of cells in the cortical and spinal components of the circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the motor performance of PD patients degrades with task completion far more easily during sequential opposition of individual finger movements than during non-individual finger oppositions. 28 The dynamics underlying movements of PD patients was, therefore, investigated by recording 10 s bouts of individual finger tapping movements. These movements were repetitive index-thumb oppositions, instructed to be of large constant amplitude, produced smoothly and rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our results point to the central role of dwelling in the context of temporal synchronization. Interestingly, several clinical studies have reported an increased DT in sequential and repeated movements in Parkinson's disease patients compared with control subjects (Agostino et al 2003;Brontë-Stewart et al 2000;Jones et al 1992;Onla-or and Winstein 2001). Franco and Turner (2012) have shown that the selective blockage of dopamine transmission in monkey sensorimotor striatum leads to increased waiting times in the transition between cued reaching movements and selfinitiated, return movements.…”
Section: Discussionmentioning
confidence: 99%